Incidence of alexithymia in worsening symptoms and quality of life of Systemic Lupus Erythematosus patients (SLE) - Fabio Rapisarda; Concetta Mezzatesta; Antonina Butticè; Alessandro Raffa; Stefano Boca (Journal of Affective Disorders Reports)
Background and Objectives: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune inflammatory disease affecting connective tissues, with the potential to impact various organs and systems, thereby limiting the quality of life for affected individuals given that it influences their psychological well-being. Indeed, various stress-inducing factors can lead to alterations in emotional regulation, often presenting, as difficulties in identifying and describing emotions, such as those associated with alexithymia. The aim of the present study is to investigate a potential correlation between the incidence of alexithymia and the worsening of symptoms, subsequently influencing the quality of life in individuals with SLE. Materials and Methods: For the realisation of the study a sample of 53 Systemic Lupus Erythematosus (SLE) patients, 47 females and 6 males, aged 16–59 years, was examined and compared with a control group (55 healthy subjects, aged 20–65). The group of patients was recruited within the Connetiviti outpatients’ clinic of the UOC (Complex Oparational Unit) of Rheumatology of the Paolo Giaccone University Polyclinic in Palermo, consisting of healthy subjects and/or with known diagnoses identified within non-clinical contexts, chosen randomly (statistical sense) in order to better represent the general population of the territorial context.Specific psycho-diagnostic measures were administered: Toronto Alexithymia Scale (TAS-20), Response Evaluation Measure (REM-71),Attachment Style Questionnaire (ASQ), Eysenck Personality Inventory (EPI),Symptom Check list (SCL-90), Short Form (SF-36). The selection of these instruments allowed us to assess attachment styles, the presence of maladaptive personality traits, defence mechanisms employed, in order to define any symptoms indicative of a psychiatric diagnosis, and evaluate the quality of life in relation to the severity of the pathology. Results: Comparisons between the two groups revealed significant differences in the Systemic Lupus Erythematosus (SLE) patients, compared to the control group, about the difficulty in identifying feelings and distinguishing them from the bodily sensations accompanying emotional activation, the use of conversion as a defence mechanism and the production of positive symptoms.Moreover, in the same group, the difficulty in identifying emotions was correlated with quality of life, since those who have difficulty identifying emotions have a poorer quality of life.Further analysis regarding the construct of alexithymia, within the patient group alone, revealed a tendency towards somatisation and the use of immature defence mechanisms, including conversion, acting out, projection, dissociation and displacement, highlighting a tendency to act out and project emotional suffering.Furthermore, there appeared to be difficulty in sharing emotional distress with others, indicating a deep sense of insecurity and a need for approval, as well as an incidence in the perception of the state of illness leading to a decline in the quality of life. Conclusions: The study demonstrated that difficulties relating to the identification and processing of emotions impact the disease presentation, influencing the worsening of symptoms and, overall, compromising the patients' quality of life.